Antibiotic-induced loss of gut microbiome metabolic output correlates with clinical responses to CAR T-cell therapy - Prasad, Rishika; Rehman, Abdur; Rehman, Lubna; Darbaniyan, Faezeh; Blumenberg, Viktoria; Schubert, Maria-Luisa; Mor, Uria; Zamir, Eli; Schmidt, Sabine; Hayase, Tomo; Chang, Chia-Chi; McDaniel, Lauren; et al. (Blood, 2025)
Antibiotic (ABX)-induced microbiome dysbiosis is widespread in oncology, adversely affecting outcomes and side effects of various cancer treatments, including immune checkpoint inhibitors and chimeric antigen receptor T-cell (CAR-T) therapies. In this study, we observed that prior exposure to broad-spectrum ABXs with extended anaerobic coverage such as piperacillin-tazobactam and meropenem was associated with worse anti-CD19 CAR-T therapy survival outcomes in patients with large B-cell lymphoma (N = 422) than other ABX classes. In a discovery subset of these patients (n = 67), we found that the use of these ABXs was in turn associated with substantial dysbiosis of gut microbiome function, resulting in significant alterations of the gut and blood metabolome, including microbial effectors such as short-chain fatty acids (SCFAs) and other anionic metabolites, findings that were largely reproduced in an external validation cohort (n = 58). Broader evaluation of circulating microbial metabolites revealed reductions in indole and cresol derivatives, as well as trimethylamine N-oxide, in patients who received ABX treatment (discovery, n = 40; validation, n = 28). These findings were recapitulated in an immune-competent CAR-T mouse model, in which meropenem-induced dysbiosis led to a systemic dysmetabolome and decreased murine anti-CD19 CAR-T efficacy. Furthermore, we demonstrate that SCFAs can enhance the metabolic fitness of CAR-Ts, leading to improved tumor killing capacity. Together, these results suggest that broad-spectrum ABX deplete metabolically active commensals whose metabolites are essential for enhancing CAR-T efficacy, shedding light on the intricate relationship between ABX exposure, microbiome function and their impact on CAR-T efficacy. This highlights the potential for modulating the microbiome to augment CAR-T immunotherapy. This trial was registered at www.clinicaltrials.gov as #NCT06218602.